The establishment of the Syrian Orthodox Patriarchate press - Taşğın, Ahmet; Langer, Robert (Historical aspects of printing and publishing in languages of the Middle East, 2014)
"The Establishment of the Syrian Orthodox Patriarchate Press" published on 01 Jan 2014 by Brill.
Gesehen am 22.02.2021